2014
DOI: 10.1111/jeb.12546
|View full text |Cite
|
Sign up to set email alerts
|

Bergmann's Rule rules body size in an ectotherm: heat conservation in a lizard along a 2200‐metre elevational gradient

Abstract: Bergmann's Rule predicts larger body sizes in colder habitats, increasing organisms' ability to conserve heat. Originally formulated for endotherms, it is controversial whether Bergmann's Rule may be applicable to ectotherms, given that larger ectotherms show diminished capacity for heating up. We predict that Bergmann's Rule will be applicable to ectotherms when the benefits of a higher conservation of heat due to a larger body size overcompensate for decreased capacity to heating up. We test this hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 63 publications
(91 reference statements)
3
70
2
Order By: Relevance
“…As such, Bergmann's rule is consistent here as a result of the role of thermal inertia due to body size (Gaston and Blackburn, 2000) and the thermoregulatory ability of these ectotherms. Also, our findings are in agreement with those of Zamora-Camacho et al (2014), who studied different populations of Psammodromus algirus inhabiting an altitudinal gradient. These authors found that thermal inertia is relevant for cooling rather than heating rates.…”
Section: D O N O S O B a R R O S I L J O S E I L M A R T O R supporting
confidence: 82%
See 3 more Smart Citations
“…As such, Bergmann's rule is consistent here as a result of the role of thermal inertia due to body size (Gaston and Blackburn, 2000) and the thermoregulatory ability of these ectotherms. Also, our findings are in agreement with those of Zamora-Camacho et al (2014), who studied different populations of Psammodromus algirus inhabiting an altitudinal gradient. These authors found that thermal inertia is relevant for cooling rather than heating rates.…”
Section: D O N O S O B a R R O S I L J O S E I L M A R T O R supporting
confidence: 82%
“…The differences between the ways of measuring heating and cooling rates (constants versus net gain or loss) may be related to the scale of the results obtained, being larger in the case of the thermal time constants and therefore more notable. Another possible reason for the differences in the results between the present study and that of Zamora-Camacho et al (2014) is the type of function for obtaining heating and cooling rates used, as they used a linear increment (or decrement) whereas we used a exponential curve. To some extent, heating and cooling rates of L. goetschi lizards reflect the solar radiation availability in the environments they inhabit, being slower at heating and/or cooling at higher latitudes, in relation to the cloudiness in the area (data not shown, see Moreno Azócar et al, 2015).…”
Section: D O N O S O B a R R O S I L J O S E I L M A R T O R contrasting
confidence: 38%
See 2 more Smart Citations
“…In fact, lizards from this system selected similar body temperatures in a laboratory thermal gradient, regardless of their elevational provenance (Zamora-Camacho et al, submitted). Therefore, lizards in the highest elevations seem to have adaptations such as darker dorsal color (Reguera et al, 2014) and larger body size (Zamora-Camacho et al, 2014b) that may allow them to cope with low environment temperature. Consequently, given that lizards from different elevations show similar body temperature, it is not surprising that they also show similar maximal sprint speed in experiments under controlled body temperature (32°C; Zamora-Camacho et al, 2014a).…”
Section: Introductionmentioning
confidence: 98%